KEARIFAN LOKAL MASYARAKAT DUSUN TEKALONG DESA SETIA JAYA DALAM MENJAGA KEBERADAAN TEMBAWANG DI KECAMATAN TERIAK KABUPATEN BENGKAYANG - Yopita, Yopita; Roslinda, Emi; Idham, M (JURNAL HUTAN LESTARI, 2020)
Tembawang is a form of land management carried out by the Dayak people in West Kalimantan. The exixtence of Tembawang in Tekalong Hamlet is still well preserved, it is suspected that the community is carrying out local wisdom in its management. This study aims to describe the forms of local wisdom that consist of knowledge, norms, regulations, and skills in Tekalong Village, Setia Jaya Village in tembawang management. The study was conducted using a survey method that is descriptive with interview techniques and questionnaire aids in the form of a list of questions submitted to a number of people (respondents). Respondents in this study were 30 people. There are 4 tembawang in Tekalong Hamlet, namely Tembawang Tekalong, Tembawang Sunge Tangket, Tembawang Bangkaris, and Tembawang Madas. The results of this study indicate that there are (5) forms of local wisdom that support the management of tembawang in Tekalong Hamlet, namely : (1). Knowledge, apply customary law to every violatoin both intentionally or unintentionally, the community also believes in several myths to be used as role models in managing Tembawang. (2). Norm, there are certain days the people cut Tembawang location. (3). Regulations, no trees can be cut down in Tembawang, and may not carry out activities that can damage the ecosystem that is in Tembawang. (4). Skills, the community utilizes the Tembawang land by planting fruit-producing trees, and (5). Trust, the presence of a ghost (Kuntilanak) who was killed, the myth of the worm king who became a watchman on Tembawang, may not build a house/sacred landKeywords : Local Wisdom,Â  Indigenous people,Â Tembawang